A CROSS-SECTIONAL SURVEY IDENTIFYING THE BACTERIAL ETIOLOGY OF INTESTINAL DISORDERS IN HIV-INFECTED PATIENTS - Israa Sami Othman; Abbas AbdulWahhab Jumaah; Khaleel Ibrahim Ismael; Dr. Amal Abdel Wahed Mohammed Mashhadani; Dr. Ali Qais Abdulkafi (Scholar Express Journals, 2022)
Gastrointestinal disorders are very common in people with HIV, which can lead to death. Several etiological factors and pathophysiological mechanisms have been proposed to cause this condition, and this study was aimed at identifying the bacterial etiology of intestinal disorders in HIV-infected patients to Iraqi patients. A cross-sectional study was established in Iraq in different hospitals to patients infected with HIV, where 100 patients were recruited, and they were distributed into two groups (70 patients, 30 control. In this study, a survey was conducted on patients whose ages ranged between 15 years and 55 years
Keywords: Gastrointestinal; E. histolytica/dispar; spending; Ethology